Metodología para el establecimiento de un sistema de evaluación en asignaturas de geografía en la educación superior (Geosaberes, 2011)
The formative evaluation and the instruments used for it is the main focus of this article which fundamentally aims to expand the methodology (based on research – action process) to establish evaluation systems for evaluating subjects on Geography in universities. There is a process to be followed in establishing the methodology, in particular, the analysis of related variables and assessment of the evaluation tools. Also, the article includes the examples of use. Therefore, the obtain results supports the implementation of the assessment system and it’s continues feedback what, accordingly, permits the use of this system in other academic subjects.